Comparative Legal Analysis of International and National Legal Norms Regulating the Protection of Personal Data - Ilyassova, G.A.; Tilep, T.S. (Bulletin of the Karaganda University “Law Series”, 2025)
The research aims to summarize the development of national norms by analyzing international standards that lawfully regulate the protection of personal data, one of the issues in safeguarding the rights and freedoms of individual. It emphasizes the importance of Kazakhstan’s accession to international instruments protecting personal data. The relevance of the research is determined by the problem of ensuring data security, which at the present stage has become a priority issue. The law has revealed instances that pose risks, particularly due to the absence of the clear provisions regulating the storage of citizen’s personal data. The authors highlight that with the rapid development of digitalization in Kazakhstan, cases of personal data dissemination have in creased, underscoring the necessity of improving national legal norms. Furthermore, the research raises issues of exercising control over the use of personal data and strengthening liability in cases of unlawful dissemina tion. Due to the weakness of the current legal mechanism for the protection of personal data, cybercrime is gaining momentum in society, negatively affecting citizens. One of the solutions to the problem is the improvement of national legislation that lawfully regulates the protection of personal data. Within the scope of the study, the authors formulated proposals for the establishing legal mechanisms in the current legislation to regulate the procedures for processing, storing, and destroying personal data, as well as for addressing ac tions related cto their preservation.